Body and sacred place in medieval Europe, 1100 - 1389 - Hayes, Dawn Marie 1968- (Studies in medieval history and culture, 2003)
Learned conceptions of sacred place : building and body as two facades of Christian worship in the twelfth and thirteenth centuries -- History incarnate : human bodies and ideal sacred place in The miracles of Our Lady of Chartres -- Earthly uses of heavenly spaces : non-liturgical activities in sacred place -- Body as champion of church authority and sacred place : the murder of Thomas Becket -- Conclusion: Division and decomposition -- Epilogue: Body and sacred place in the wake of September 11 : resurrecting medieval metaphors in the modern world